THE PROBLEM OF TERRORISM IN INTERNATIONAL RELATIONS - Shokhida, Kodirova (Antis Publisher, 2024)
To date, taking into account the existing parameters of international terrorism, it has become characterized by a long-term and sustainable nature. The processes of further development of international terrorism and the constant increase in the degree of its social danger for all humanity are expected to largely depend on the possibility of maintaining and the intensity of the impact of its existing features, as well as on the positive potential of the world community aimed at minimizing them. The article states that the achievement of the goals of terrorist acts is ensured through psychological influence also on persons who are not direct victims of terrorist violence. The choice of such victims is carried out more within the framework of their symbolic than actual meaning. The author has determined that currently the main problem is the qualitative strengthening of the negative potential of the current system of international terrorism based on the use, to varying degrees, of high technologies for the mass destruction of humanity. At the same time, it should be recognized that it does not yet have any complete character from the position of complete mastery by subjects of international terrorism of key actually existing similar technologies, which may indicate further attempts to fully master them. It is concluded that within the framework of the formation of theoretical prerequisites for the fight against international terrorism, it is relevant to focus on assessing the extent to which the policy and strategy of the fight against terrorism in the system of international relations are capable of identifying the operational and strategic capabilities of terrorists.